2015
DOI: 10.3109/02699052.2015.1053526
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and selenium reduce plasma cytokine and brain oxidative stress levels in diabetic rats

Abstract: Melatonin and selenium induced protective effects against diabetes-induced brain and erythrocyte oxidative injuries through regulation of the antioxidant level and cytokine production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Melatonin also showed its antioxidant effect by decreasing malondialdehyde level and increasing glutathione level, superoxide dismutase, catalase, and glutathione‐S‐transferase activities. Baydas et al and Kahya et al found similar results showing that melatonin decreased lipid peroxidation and increased glutathione level in the brain tissue of diabetic rats . In histological evaluation, rats treated with melatonin revealed decreased neuronal degeneration when compared with the diabetic rats.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Melatonin also showed its antioxidant effect by decreasing malondialdehyde level and increasing glutathione level, superoxide dismutase, catalase, and glutathione‐S‐transferase activities. Baydas et al and Kahya et al found similar results showing that melatonin decreased lipid peroxidation and increased glutathione level in the brain tissue of diabetic rats . In histological evaluation, rats treated with melatonin revealed decreased neuronal degeneration when compared with the diabetic rats.…”
Section: Discussionmentioning
confidence: 64%
“…In this study, melatonin was also added to the insulin treatment showing that melatonin decreased lipid peroxidation and increased glutathione level in the brain tissue of diabetic rats. 81,82 In histological evaluation, rats treated with melatonin revealed decreased neuronal degeneration when compared with the diabetic rats. Main differences between the effects of melatonin alone and insulin alone treatments were observed in glutathione level, glutathione-S-transferase, myeloperoxidase, and TF activity and in histopathological scores.…”
Section: Histological Resultsmentioning
confidence: 99%
“…CGRP is a pain-transmitting neuropeptide present in the DRG, which is always up-regulated in pain conditions 72. TNF-α and IL-1β are critical Mel-mediated molecules in neuro-inflammation 53, 73, and their expression is associated with neuronal excitability and sensitization 74, 75. Our results indicated that cuff implantation increased the expression of c-fos , CGRP, and the inflammatory cytokines TNF-1α and IL-1β, which indicated pain sensation after cuff implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Brain samples were obtained and prepared as previously described (Dilek et al 2010;Senol et al 2014;Kahya et al 2015). The removed tissues of brain cortex samples were washed twice with cold physiological saline.…”
Section: Preparation Of Brain Samplesmentioning
confidence: 99%
“…Plasma cytokine [TNF-α, interleukin (IL)-1β, and IL-4] levels were measured using a commercial enzyme-linked immunosorbent assay (ELISA), following the manufacturer's instructions as described in previous studies (Senol et al 2014;Kahya et al 2015) (Multimode microplate reader, Infinite® 200 PRO series, Männedorf Switzerland). They employ the quantitative sandwich techniques.…”
Section: Cytokine Determinations In Plasmamentioning
confidence: 99%